Private corruption in Brazil - Chaves, Anna Cecília Santos (2014)
This paper aims to discuss the private corruption according to national law. To reach this goal, we seek to initially define its conceptual framework, starting the analysis from the general concept of corruption. After, we intent to examine the treatment given to private corruption in international law and foreign law. These assumptions try to draw a picture, albeit imprecise, given the paucity of statistical data and academic studies about private corruption in Brazil. We also discuss, in this paper, about the legal instruments for repression of this kind of corruption available in our juridical system, analyzing its elements and its practical efficiency in the protection of legal interests that gave rise to its creation. We also analyse the effectiveness of criminal law as an instrument of repression of this kind of corruption, compared to other instruments available in the Brazilian juridical order.